Konsep keadilan dalam jual beli islam: memahami hak dan kewajiban pedagang dan pembeli - Ramadhoni, Nurul (Maliki Interdisciplinary Journal, 2025)
This article disccusses justice in Islamic trade, focusing on the rights of merchants, the rights of buyers, the principle of voluntary agreement, and the business ethics applied in transactions. From an Islamic perspective, trade (al-bai’) is not merely an exchange of goods and money, but an interaction that requires honesty, transparency, and adherence to Sharia. Merchants have the rihgt to earn profits, but they are obliged to act fairly and transparently toward buyers, Buyers have the right to receive goods according to the agreement but are required to pay the agreed price in good faith. The principle of voluntary agreement emphasizes that transactions must be conducted without coercion and based on mutual consent. Implementing justice enhances consumer trust, reduces potential disputes, and fosters healthy business ethics. This study asserts that justice in islamic business transactions is not only a moral norm but also a fiqh-based guideline that ensures economic practices are fair, transparent, and mutually beneficial.